Hispidin and Lepidine E: Two Natural Compounds and Folic Acid as Potential Inhibitors of 2019-novel Coronavirus Main Protease (2019- nCoVMpro), Molecular Docking and SAR Study - Serseg, Talia; Benarous, Khedidja; Yousfi, Mohamed (Current Computer - Aided Drug Design, 2021)
Background: 2019-nCoVis, a novel coronavirus was isolated and identified in 2019 in the city of Wuhan, China. On February 17, 2020 and according to the World Health Organization, 71, 429 confirmed cases worldwide were identified, among them 2162 new cases were recorded in the last 24 hours. One month later, the confirmed cases jumped to 179111, with 11525 new cases in the last 24 hours, with 7426 total deaths. No drug or vaccine is present at the moment for human and animal coronavirus. Methods: The inhibition of 3CL hydrolase enzyme provides a promising therapeutic principle for developing treatments against CoViD-19. The 3CLpro (Mpro) is known for involving in counteracting the host innate immune response. Results: This work presents the inhibitory effect of some natural compounds against 3CL hydrolase enzyme, and explains the main interactions in inhibitor-enzyme complex. Molecular docking study was carried out using Autodock Vina. By screening several molecules, we identified three candidate agents that inhibit the main protease of coronavirus. Hispidin, lepidine E, and folic acid are bound tightly in the enzyme, therefore strong hydrogen bonds have been formed (1.69-1.80Å) with the active site residues. Conclusion: This study provides a possible therapeutic strategy for CoViD-19.
Keywords: 2019-nCoV protease